Barriers and motivators to blood donation among university students in Japan: development of a measurement tool. Issue 3 (11th May 2013) - Ngoma, A. M.; Goto, A.; Yamazaki, S.; Machida, M.; Kanno, T.; Nollet, K. E.; Ohto, H.; Yasumura, S.
Abstract : Background and Objectives: Despite growing demand for transfusion, the number of voluntary young blood donors has steadily decreased over recent years in Japan. This study aimed to develop an easy‐to‐use survey tool to assess barriers and motivators to blood donation among Japanese university students. Materials and Methods: We conducted cross‐sectional studies at two universities in Fukushima Prefecture, Japan, in December 2011 (Stage 1) and February 2012 (Stage 2) using self‐administered questionnaires. A short list of motivators and barriers to blood donation was developed from the open‐ended questions asked of 50 students in Stage 1. In the Stage 2, we asked 105 students how important these items were when they decided whether or not to donate blood. Items showing a significant difference between donors and non‐donors were kept in the final list. Results: Overall, 56% of the 100 participants analysed in Stage 2 were men, and ages ranged from 19 to 24 with a median of 20 years. Comparison of motivators and barriers between donors and non‐donors revealed that only barrier item 8 ('Frightened by blood donation') showed a significant difference ( P  = 0·0006) in an expected direction and with a consistency between two universities. Conclusions: This study identified fear as being the most significant barrier to blood donation among Japanese university students, which could be used as a single convenient indicator to assess their readiness to donate. More academic and clinical efforts are needed to understand and address students' fear towards blood donation in order to increase the donor pool in Japan.